Analysis of the Role of Parents on Children's Physical Growth of 4-5 Years at Dharma Wanita Tosaren II Kediri City - Wening Palupi Dewi; Arina Chusnatayaini (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Physical growth in children is influenced by various factors such as heredity (ethnicity, race, sex), nutrition, culture, environment, socioeconomic status, climate, physical activity, health, hormones, and particularly the role of parents in fulfilling nutritional needs. This study aimed to examine the influence of parental roles on the physical growth of children aged 4–5 years at Kindergarten Dharma Wanita Tosaren II, Kediri. Using a correlational analytic design with a cross-sectional approach, the study involved 70 parents selected through total sampling. Data on the independent variable (parental role) and dependent variable (physical growth indicators) were collected via questionnaires and observation sheets, and analyzed using the Spearman correlation test.